Kampanye Capres dan Cawapres Pada Pemilu 2019: Efektivitas Penggunaan Buzzer di Media Sosial - La Ode Muhammad Idris; Reza Fahlevi (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2022)
Campaign is an important component for candidate pairs as one of the main strategies in achieving the target vote. In the 2019 election, for example, the increasingly widespread use of social media was used as an effective way to communicate politically to the public. The public is presented with various campaign concepts, ranging from using official accounts to using paid accounts to increase conversations on social media. Indeed, in the campaign concept, the presentation of the concept of vision and mission has a neat and competent structure, but this has been eroded by the number of robotic accounts that only present information on activities to the movements of candidate pairs in each campaign action. This article uses a qualitative descriptive analysis design with a literature study method. This writing will use the Uses and Gratification Theory approach where in the explanation of this theory focuses on research conducted on viewers or audiences as a determinant of message and media selection. The existence of a buzzer that is owned by each pair of candidates, does influence the vote and the audience's desire to vote, but the audience in this case is the people who have the right to choose and still use their hearts and minds to make their choice. Keywords: campaign, election, voters, social media, democracy Campaign is an important component for candidate pairs as one of the main strategies in achieving the target vote. In the 2019 election, for example, the increasingly widespread use of social media was used as an effective way to communicate politically to the public. The public is presented with various campaign concepts, ranging from using official accounts to using paid accounts to increase conversations on social media. Indeed, in the campaign concept, the presentation of the concept of vision and mission has a neat and competent structure, but this has been eroded by the number of robotic accounts that only present information on activities to the movements of candidate pairs in each campaign action. This article uses a qualitative descriptive analysis design with a literature study method. This writing will use the Uses and Gratification Theory approach where in the explanation of this theory focuses on research conducted on viewers or audiences as a determinant of message and media selection. The existence of a buzzer that is owned by each pair of candidates, does influence the vote and the audience's desire to vote, but the audience in this case is the people who have the right to choose and still use their hearts and minds to make their choice. Keywords: campaign, election, voters, social media, democracy